GREEDY ALGORITHM IN GREEDY REDUCTION EDUCATION GAME BASED ON ANDROID PLATFORM - Bagus Satrio Waluyo Poetro; Nurul Hidayah; Suryani Alifah (Universitas Islam Sultan Agung, 2018)
The greedy algorithm is one of the simplest algorithms to solve the optimization problem. The greedy algorithm is able to solve the problem quickly. Greedy Reduction game is a game of mathematical reduction that uses the theory of greedy algorithm in the process of determining the player's victory in playing the game. Players who play this game have to answer the problem by solving the reduction operation with subtracting the number by selecting available numbers on the game, until it reaches the specified number of questions. Players will either win the game or produce a serial number if the numbers the player chooses to subtract fewer numbers from the numbers used by greedy. Tests conducted on this research is to use black box testing method. Based on the tests performed, greedy algorithm can be applied in solving the existing problems in Greedy Reduction game.